The Influence of Service Quality and Doctor Communication on Patient Satisfaction and Loyalty in RSUD Dr. Soeroto Ngawi - Fiany Calista Wahyudiana; Nuryakin .; Nur Hidayah (Assosiasi Dosen Muhammadiyah Magister Administrasi Rumah Sakit Indonesia, 2022)
Service quality assessment is critical because low service quality is supposed to cause low patient satisfaction. A doctor's communication and presence that is not on time is considered a factor that causes the low quality of service to outpatients. This attitude creates the impression of unresponsiveness in serving patients' needs and reducing patient loyalty. This study aims to identify the influence of service quality and doctor's communication partially and simultaneously on patient satisfaction and loyalty. This research is quantitative research with a cross-sectional approach. The sampling technique was purposive sampling with a sample of 40 outpatients who had made return visits at least twice. The data analysis technique started with univariate and bivariate analysis using multiple linear regression and hypothesis testing. The results of this study revealed that, individually, the service quality and doctor's communication variables significantly affect patient satisfaction and loyalty; concurrently, the variables of service quality and doctor's communication also significantly influence patient satisfaction and loyalty.